PARTISIPASI ORANGTUA DALAM PENYELENGGARAAN PAUD PADA MASYARAKAT NELAYAN DI TK AL IKHLAS KARANGANTU SERANG – BANTEN - Erien Nabila Putri; Luluk Asmawati; Fadhlullah Fadhlullah (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2021)
This study aims to determine how the participation of parents in implementing early childhood education at TK Al Ikhlas Karangantu. The benefit of this research is to provide knowledge about parental participation in PAUD implementation. The research method used is a case study qualitative research method. Data collection techniques were carried out by means of observation, interviews, field notes, documentation and questionnaires. Data analysis used data reduction, data presentation and conclusion drawing. It can be seen from the results of research on parental participation in implementing PAUD at TK Al Ikhlas Karangantu that it has been going well, the number of parents who participate in every activity shows that parental participation is going very well. Forms of parental participation in the form of: Participation in decision making, participation in implementation, participation in making and participation in evaluation. Communication between the school and parents runs very smoothly, this is also one of the supporting factors that affect parental participation.